The sludge-based adsorbent from oily sludge and sawdust preparation and optimization - Du, Mingming (Environmental technology, 2021)
Sludge-based adsorbent (S-AB) converted by oily sludge can make full use of the precious resource. In this paper, oily sludge and discarded sawdust are used to prepare adsorbent through chemical activation. The adsorbent prepared is used to adsorb raw petroleum. Firstly, the most reasonable chemical activator ZnCl2 is ascertained through parallel comparative experiments. The characterization results of N2-adsorption are consistent with adsorption experiment results, which shows that higher mesopore surface area and volume are benefitted by the adsorption process. Secondly, the optimization of preparation technology is investigated through orthogonal experiments after parallel comparative experiments. The adsorption capacity of S-AB-ZnCl2 is stronger when the preparation conditions are as follows: an activation temperature of 550°C, an activation time of 3.5 h, a solid-liquid ratio of 1:1.5, a sludge-sawdust ratio of 1:0.5 and the heating rate of 15°C/min. The maximum quantity adsorbed Q0 = 434.78 mg/g, calculated through the Langmuir adsorption isothermal models, of S-AB-ZnCl2 prepared under optimized condition is higher than that before optimization. In addition, the most reasonable kinetics fits were of the second-order model